The Climate-Smart Village approach: putting communities at the heart of restoration - Sanogo, Diaminatou; Sall, Moussa; Camara, Baba Ansoumana; Diop, Mouhamadou; Badji, Marcel; Ba, Halimatou Sadyane (Tropenbos International, 2020)
Land degradation affects 24% of the world’s land surface and 1.5 billion of its people. It is the result of human activities, exacerbated by natural processes, and is closely linked to climate change and loss of biodiversity. In Africa two-thirds of arable land is degraded. In Senegal, 2.5 million hectares are degraded (CSE 2011); the central “groundnut basin” is particularly affected. Increasing the capacity of smallholders to address land degradation and adapt to climate variation is paramount, which is why the Senegalese Institute for Agricultural Research (ISRA) and its partners adopted the holistic and participatory “climate-smart village” approach. Based on innovative local governance, this approach includes seven components: (1) climate forecasts and information; (2) resilient crop varieties and good agricultural practices; (3) agroforestry with fruit and fodder species; (4) farmer managed natural regeneration; (5) inter-village silvopastoral areas; (6) planting of native fruit trees; and (7) small forestry and farm businesses.